Analysis of broad-band piezoelectric sandwich transducer with perforated structure - LI, Chong-Mao; HOU, Li-Qi; YING, Chung-Fu (Archives of Acoustics, 1984)
Pre-stressed piezoelectric sandwich transducers are used widely as sonic source for many low frequency ultrasonic applications, notably in the fields of macrosonics sand sonar. For certain applications a broader bandwidth is necessary. The sandwich transducer with perforated structure developed by us is formed by drilling holes longitudinally in the radiating head, and has been shown experimentally to possess a bandwidth approximately double that of a conventional nonperforated transducer, while its electroacoustic efficiency remains almost undeteriorated [1]. In this paper a theoretical model for the broadband structure is proposed. The frequency characteristics of the input electrical admittance of the transducer and the input mechanical impedance of the radiating head loaded by water, are calculated both as functions of the relative cross-section a of the bored part and the relative depth of the holes β of the radiating head. Some theoretical results are compared with measured ones, the two fairly well agree.